The Effect of Customer Number and Inflation Level on Pawn Financing at the Agus Salim Sharia Service Unit (UPS) of Gorontalo City - Iftita Maryam Nur Karim; Niswatin Niswatin; Ivan Rahmad Santoso (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of the number of customers and the inflation rate on rahn (pawn) financing at the Sharia Pawnshop, Sharia Service Unit (UPS) Agus Salim, Gorontalo City, by incorporating a COVID-19 pandemic dummy variable to distinguish between conditions during and after the pandemic. This quantitative study uses secondary data sourced from Sharia Pawnshop's internal reports and the Central Statistics Agency for the period 2019-2024. The sample consisted of 72 months of observations. Data analysis was conducted using multiple linear regression with a dummy variable as a control variable, along with classical assumption tests, utilizing EViews version 13. The results indicate that, partially, neither the number of customers nor the inflation rate has a significant effect on rahn financing. However, simultaneously, both variables have a significant combined effect. Furthermore, a significant difference exists between the pandemic and post-pandemic periods, with the distribution of rahn financing increasing in the post-pandemic period.